A comparative study on green wall construction systems, case study: South valley campus of AASTMT. (June 2022) - El Menshawy, Adel Samy; Mohamed, Abdelaziz Farouk; Fathy, Nayera Mahmoud
Abstract: Cities are experiencing a rapid expansion causing environmental, economic and social concerns that are compromising the human's welfare and the sustainability of cities. The urbanization process has been destructing the green areas, and due to increasing the land value, it became very difficult to plant horizontally. This causes catastrophic impacts on our environment that suffers from an unbearable concrete chaos. Several studies have shown that, introducing green walls to the construction field, is a promising design approach that can bring a large surface of vegetation on a relatively small footprint and they can greatly contribute in enhancing and restoring the urban environment as well as improving the building's thermal performance and decreasing albedo. Thus, this paper aims to provide a comparative study on green wall construction systems, in addition to; shedding light on innovative studies regarding green walls' benefits and addressing important design considerations through inductive and deductive methodologies. Then, it analyzes Aswan's AASTMT as a local case study in Upper Egypt for applying the previously formulated framework through a field survey. The findings reveal that the presence of green walls has resulted in: providing greater green area coverage (4765 m 2 ) compared to the building's footprint (3250 m 2 ), reducing the high energy consumption and the overall high energy costs, altering the adjacent micro-climate and improving the air quality, enhancing the aesthetic appeal and creating a distinctive sense of place indoors and outdoors, increasing the workability and productivity of users, enhancing the biodiversity of Aswan, and reducing the noise pollution.